Math at eNotes
http://www.enotes.com/math
The latest questions and answers, from members following Math at eNotes.Sat, 25 Oct 2014 07:19:59 PSTen-usThe equation `log_3 (12n-1) - log_3 (2n+7) = 2` has to be solved for n....
http://www.enotes.com/homework-help/log3-12n-1-log3-2n-7-2-find-value-n-255097
The equation `log_3 (12n-1) - log_3 (2n+7) = 2` has to be solved for n. Use the relation, `log a - log b = log(a/b)` . `log_3 (12n-1) - log_3 (2n+7) = 2` gives: `log_3((12n-1)/(2n+7)) = 2` Now `log_a b = c` implies `b = a^c` . `log_3((12n-1)/(2n+7)) = 2` implies `(12n-1)/(2n+7)) = 3^2 = 9` `12n - 1 = 9*(2n+7)` `12n - 1 = 18n + 63` `6n = -64` `n = -64/6` `n = -32/3` But `log_3 (12n-1)` and `log_3 (2n+7)` are not defined for `n = -32/3` . The...http://www.enotes.com/homework-help/log3-12n-1-log3-2n-7-2-find-value-n-255097Sat, 25 Oct 2014 07:19:59 PSTThe function f(x) = 7x^3+4. To determine the inverse function `f^-1(x)`...
http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471975
The function f(x) = 7x^3+4. To determine the inverse function `f^-1(x)` , rewrite y = 7*x^3 + 4 in a form where x is expressed in terms of y. `y = 7*x^3 + 4` `(y - 4) = 7*x^3` `(y - 4)/7 = x^3` `x = ((y - 4)/7)^(1/3)` Now interchange x and y, `y = ((x - 4)/7)^(1/3)` This gives the inverse function of `f(x) =7x^3+4` as `f^-1(x) = ((x - 4)/7)^(1/3)`http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471975Sat, 25 Oct 2014 07:08:08 PSTSee the answer posted for the same user:...
http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471975
See the answer posted for the same user: http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471976http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471975#1Fri, 24 Oct 2014 19:12:16 PSTOne way to find the inverse function is to exchange the roles of x and...
http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471976
One way to find the inverse function is to exchange the roles of x and y, and then solve for the new y. This works because the graph of the inverse of a function is the reflection of the graph of the function over the line y=x. So ` ``f(x)=7x^3+4 ==> y=7x^3+4 ` Exchanging x and y we get: `x=7y^3+4 ` Now solve for y: `7y^3=x-4 ` `y^3=(x-4)/7 ` `y=root(3)((x-4)/7) ` So `f^(-1)(x)=root(3)((x-4)/7) `...http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471976Fri, 24 Oct 2014 19:08:04 PSTFind the inverse of the function f(x)=7x^3+4
http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471976
Find the inverse of the function f(x)=7x^3+4http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471976#2October 24, 2014, 6:47 pm PSTfind the inverse of the function F(x)=7x^3+4
http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471975
find the inverse of the function F(x)=7x^3+4http://www.enotes.com/homework-help/find-inverse-function-f-x-7x-3-4-471975#3October 24, 2014, 6:42 pm PST(3*sin x + 1)^3 You first have to do the power rule, moving the exponent...
http://www.enotes.com/homework-help/use-chain-rule-find-derivative-3-sin-x-1-3-470459
(3*sin x + 1)^3 You first have to do the power rule, moving the exponent to the front, as a coefficient, and then changing the exponent to one number lower than the original. Keep the inside the same. 3(3*sin x + 1)^2 Now you must multiply this by the derivative of the inside terms. You have to first do the product rule to find the derivative of 3*sin x. A rule states that the derivative of sin x is cos x. 3(3*sin x + 1)^2 * (3*cos x + sin...http://www.enotes.com/homework-help/use-chain-rule-find-derivative-3-sin-x-1-3-470459Thu, 23 Oct 2014 14:52:29 PST-2(x + 5 × 7 + 3) This should to be simplified by following BODMAS...
http://www.enotes.com/homework-help/2-x-5-7-3-90739
-2(x + 5 × 7 + 3) This should to be simplified by following BODMAS (Brackets Of Division Multiplication Addition Subtraction) also known as PEMDAS (Parentheses, Exponents, Multiplication, Division, Addition, Subtraction) -2(x + 5 × 7 + 3) (first step multiply inside the brackets) -2(x+35+3) (2nd step addition inside the brackets) -2(x+38) (3rd step remove brackets by multiplying -2 with...http://www.enotes.com/homework-help/2-x-5-7-3-90739Thu, 23 Oct 2014 09:57:25 PST4(3x+7)=7 In order to solve this we need to remove the parenthesis and...
http://www.enotes.com/homework-help/solve-for-x-4-3x-7-7-87845
4(3x+7)=7 In order to solve this we need to remove the parenthesis and then isolate x to find the value of x. 4(3x+7)=7 (multiply 3x and 7 by 4 to remove the brackets) 12x+28=7 12x+28-28=7-28 (subtract 28 from both sides) 12x=-21 12x/12=-21/12 (divide both sides by 12) x=-1.75 or -21/12 Answer.http://www.enotes.com/homework-help/solve-for-x-4-3x-7-7-87845Thu, 23 Oct 2014 09:38:34 PST4x^2-16x=48 The above can be solved with the help of quadratic formula...
http://www.enotes.com/homework-help/4x-2-16x-48-solve-for-x-80513
4x^2-16x=48 The above can be solved with the help of quadratic formula for that the above equation must be turned into a quadratic equation i.e. Such that; 4x^2-16x-48=0 Where, a=4 b=-16 c=-48 We then input the above values into the quadratic formula below, and simplify it, (i have done addition and subtraction separately): x=[-(-16)+sqrt{(-16)^2-4(4)(-48)}]/2(4) [-(-16)-sqrt{(-16)^2-4(4)(-48)}]/2(4)...http://www.enotes.com/homework-help/4x-2-16x-48-solve-for-x-80513Thu, 23 Oct 2014 09:24:50 PST2x + sqrt(16+x^2)=11 In order to solve this we must first solve the sqrt...
http://www.enotes.com/homework-help/solve-equation-2x-sqrt-16-x-2-11-86685
2x + sqrt(16+x^2)=11 In order to solve this we must first solve the sqrt part 2x + sqrt(16+x^2)=11 2x + 4+x= 11 After that x should be isolated in order to solve the equation 3x +4-4=11-4 (subtracting 4 from both sides) 3x =7 3x/3 =7/3 (dividing both sides by 3) x =2.33 Answer.http://www.enotes.com/homework-help/solve-equation-2x-sqrt-16-x-2-11-86685Thu, 23 Oct 2014 09:07:38 PSTx^2 + 3x + 2 You can solve by considering it as a quadratic...
http://www.enotes.com/homework-help/how-do-solve-this-equation-x-2-3x-2-85137
x^2 + 3x + 2 You can solve by considering it as a quadratic equation x^2 + 3x + 2=0 i.e. ax^2+bx+c=0 Where a=1 b=3 c=2 Quadratic Formula, = [-3+sqrt{3^2-4(1)(2)}]/2(1) =[-3-sqrt{3^2-4(1)(2)}]/2(1) = [-3+sqrt{9-8}]/2 =[-3-sqrt{9-8}]/2 = [-3+sqrt{1}]/2 =[-3-sqrt{1}]/2 = [-3+1]/2 ...http://www.enotes.com/homework-help/how-do-solve-this-equation-x-2-3x-2-85137Thu, 23 Oct 2014 09:01:19 PSTMean is the average of the entire data set. 1,2,4,7,8,9,10,20 ...
http://www.enotes.com/homework-help/how-do-find-mean-median-mode-midrange-following-466970
Mean is the average of the entire data set. 1,2,4,7,8,9,10,20 = (1+2+4+7+8+9+10+20)/8 = 61/8 = 7.625 Median is the middle value of the entire data set. 1,2,4,7,8,9,10,20 In this case the total number of values is 8 therefore average is found for the 2 middle numbers 7 and 8 Median=(7+8)/2 =15/2 =7.5 Mode is the most...http://www.enotes.com/homework-help/how-do-find-mean-median-mode-midrange-following-466970Thu, 23 Oct 2014 07:52:18 PSTIn order to solve this through quadratic formula, we need to change it...
http://www.enotes.com/homework-help/solve-x-squared-24-11x-by-using-quadratic-formula-466701
In order to solve this through quadratic formula, we need to change it to this equation format ax^2+bx+c=0 x^2-11x+24=0 Quadratic formula Where, a=1 b=-11 c=24 x=[-(-11)+sqrt{(-11)^2-4(1)(24)}]/2(1) x=[-(-11)-sqrt{(-11)^2-4(1)(24)}]/2(1) ` ` x=[11+sqrt{121-96}]/2 x=[11-sqrt{121-96}]/2 x=[11+sqrt{25}]/2 x=[11-sqrt{25}]/2 x=[11+5]/2 x=[11-5]/2 x=16/2 x=6/2 x=8 Answer x=3 Answerhttp://www.enotes.com/homework-help/solve-x-squared-24-11x-by-using-quadratic-formula-466701Thu, 23 Oct 2014 05:50:33 PSTA linear equation is an equation between two variables that gives a...
http://www.enotes.com/homework-help/what-linear-equation-471761
A linear equation is an equation between two variables that gives a straight line when plotted on a graph.http://www.enotes.com/homework-help/what-linear-equation-471761Wed, 22 Oct 2014 10:08:07 PST